Stipa klimesii (Poaceae), a new species from Western Himalayas (India) - Nobis, Marcin; Nobis, Agnieszka; Nowak, Arkadiusz; Nowak, Sylwia (Phytotaxa, 2014)
Stipa klimesii sp. nov. from the Western Himalayas (India: Ladakh) and its variety S. klimesii var. pubescens var. nov. are described. The new species is similar to S. roborowskyi but differs by its longer anthecium, longer ligules of vegetative shoots, longer hairs on seta and shorter awns. Stipa klimesii is also similar to S. purpurea, but differs by longer ligules of vegetative shoots, shorter awns, slightly shorter hairs on seta and by the character of the panicle, which is compressed and with straight branches in S. klimesii vs. lax and with flexuous branches in S. purpurea. Epidermal patterns of the lemma in S. klimesii and both above-mentioned species, were examined by scanning electron microscopy. Images of macromorphological and micromorphological structures are provided.